Novel surgical method for the exposure and plating of dorsally displaced unstable distal radius fractures - Hrishikesh Saodekar; Yogesh Sharad Salphale; Gopal Shinde; Gaurav Bhutada; Aman Tomar; Atharva Sharma (Trauma Case Reports)
The dorsal approach to the wrist is challenging because of the high number of extensor tendons crossing the wrist joint and extensor retinaculum (ER) enveloping the distal dorsal end of the radius. Dorsal plating of the radius has gained popularity owing to the concept of fragment-specific fixation of the distal radius. Here, we describe a novel method of selectively sectioning the extensor retinaculum that ensures adequate soft tissue care and good fixation with low-profile implants with good clinico- radiological outcome.